2008
DOI: 10.1007/s11207-008-9255-z
|View full text |Cite
|
Sign up to set email alerts
|

The Recovery of CME-Related Dimmings and the ICME’s Enduring Magnetic Connection to the Sun

Abstract: It is generally accepted that transient coronal holes (TCHs, dimmings) correspond to the magnetic footpoints of CMEs that remain rooted in the Sun as the CME expands out into the interplanetary space. However, the observation that the average intensity of the 12 May 1997 dimmings recover to their pre-eruption intensity in SOHO/EIT data within 48 hours, whilst suprathermal unidirectional electron heat fluxes are observed at 1 AU in the related ICME more than 70 hours after the eruption, leads us to question wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 57 publications
3
43
1
Order By: Relevance
“…However, since we have only one view of a 3D density depletion structure, both the EUV dimming structure and the connection between EUV dimming and CME fluxrope are not clearly understood. Attempts to compare the magnetic flux in the EUV dimming regions with the corresponding in-situ ICME magnetic fluxropes have shown some, albeit moderate, success (Webb et al, 2000;Qiu et al, 2007;Attrill et al, 2008). Using a sequence of wavelet-enhanced EIT images and EIT difference images, we found that the CMEs on 5 and 16 May have also EIT double dimmings similar to the 12 May case (see attached animations eit19970505difmv.gif, eit19970512mv.gif and eit19970516difmv.gif).…”
Section: Euv Dimmingmentioning
confidence: 57%
See 1 more Smart Citation
“…However, since we have only one view of a 3D density depletion structure, both the EUV dimming structure and the connection between EUV dimming and CME fluxrope are not clearly understood. Attempts to compare the magnetic flux in the EUV dimming regions with the corresponding in-situ ICME magnetic fluxropes have shown some, albeit moderate, success (Webb et al, 2000;Qiu et al, 2007;Attrill et al, 2008). Using a sequence of wavelet-enhanced EIT images and EIT difference images, we found that the CMEs on 5 and 16 May have also EIT double dimmings similar to the 12 May case (see attached animations eit19970505difmv.gif, eit19970512mv.gif and eit19970516difmv.gif).…”
Section: Euv Dimmingmentioning
confidence: 57%
“…Symmetric double dimmings are rarely observed but attracted a lot of attention and research effort because they well represent the common interpretation, i.e., that the two dimming regions are the footprints of an expanding fluxrope still connected to the Sun and experiencing significant density depletion Webb et al, 2000;Yurchyshyn et al, 2006;Liu et al, 2007;Attrill et al, 2008). However, since we have only one view of a 3D density depletion structure, both the EUV dimming structure and the connection between EUV dimming and CME fluxrope are not clearly understood.…”
Section: Euv Dimmingmentioning
confidence: 97%
“…The gradual recovery of the EUV brightness is a typical feature of coronal dimmings (Reinard & Biesecker 2008;Attrill et al 2008), which is correlated with the overlying corona closure and heating by the confined plasma in the closed magnetic loops (McIntosh et al 2007). Attrill et al (2008) proposed a model to interpret the maintained outflows during the recovery phase in which interchange reconnections are continually occurring between emerging flux in the dimming region and the opening field lines caused by CME.…”
Section: The 2006 December 14 Eventmentioning
confidence: 97%
“…On the other side, as the gas pressure in the cavity decreases during the CME eruption, the pressure gradient is expected to drive outflow from the transition region and even chromosphere Jin et al, 2009). This process, in addition to the interchange reconnection between the stretched magnetic field and small coronal loops (Attrill et al, 2008), refills the depleted corona, making the coronal dimming recover to normal in tens of hours.…”
Section: Cavitymentioning
confidence: 99%